2008
DOI: 10.1590/s0034-89102008000100018
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos fumantes que não buscam tratamento para deixar de fumar, município do Rio de Janeiro

Abstract: É fundamental compreender que os fumantes não são iguais e que determinados fumantes precisam ser conquistados como "potenciais clientes" de programas de intervenção voltados às suas necessidades específicas. O objetivo do estudo foi comparar os perfis de fumantes recrutados para um estudo de intervenção para cessação de fumar com os da população geral de fumantes no município do Rio de Janeiro, nos anos 2002-2003. As heterogeneidades encontradas indicam que diferentes estratégias de captação associadas às int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The total acid number (TAN) is very important to evaluate the acid and corrosive power of petroleum fractions. In Brazil, the crude oils are considerably more acid in comparison to oils from other parts of the world . The TAN average for Brazilian oils is 0.64 mg KOH/g; however, some oils from Espirito Santo Basin have an acidity equal to 2.93 mg KOH/g .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The total acid number (TAN) is very important to evaluate the acid and corrosive power of petroleum fractions. In Brazil, the crude oils are considerably more acid in comparison to oils from other parts of the world . The TAN average for Brazilian oils is 0.64 mg KOH/g; however, some oils from Espirito Santo Basin have an acidity equal to 2.93 mg KOH/g .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, after the physical process of distillation, different hydrocarbon groups are produced within different temperature ranges, named fractions or cuts . In the Brazilian petroleum industry, the fraction boiling ranges are represented by different temperature intervals: residual gas (<40 °C), gasoline (40–175 °C), kerosene (175–235 °C), light gas oil (235–305 °C), heavy gas oil (305–400 °C), lubricants (400–510 °C), and residues (>510 °C). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about non-treatment seeking smokers including their level of motivation to quit smoking and their beliefs about smoking cessation. Szklo and Otero (Szklo & Otero, 2008) reported that smokers seeking treatment were more likely to be female, older, highly educated, nicotine dependent, with a longer smoking duration, and perceived their health as poor compared to non-treatment seeking smokers suggesting that these groups may differ on variables including demographic characteristics and tobacco use indices.…”
Section: Introductionmentioning
confidence: 99%
“…Estes últimos fazem parte do grupo de fumantes que procuram os programas de cessação públicos ou privados e geralmente são os mais dependentes, possuem maior carga tabágica e com várias tentativas fracassadas de abandono 3 . Assim, as características dos fumantes que procuram os serviços de saúde são diferentes daquelas da comunidade em geral e muitas delas são pouco conhecidas 4 . Apesar dos avanços alcançados com o conhecimento do tabagismo e da importância dos programas de cessação, baseados nos consensos das sociedades científicas 5 , nota--se que o tratamento do tabagismo não consegue atingir as taxas de sucesso terapêutico desejadas.…”
Section: Introductionunclassified